Dibenzo[a, e]pentalenophanes: Bending a Non‐Alternant Hydrocarbon. Issue 29 (30th April 2018) - Hermann, Mathias; Wassy, Daniel; Kratzert, Daniel; Esser, Birgit
Abstract: In cyclophanes, an aromatic moiety is incorporated into a (strained) cyclic structure. Of particular interest as model systems for bent carbon nanostructures are those containing polycyclic aromatic hydrocarbons. Dibenzo[ a, e ]pentalene (DBP) is a non‐alternant polycyclic hydrocarbon with small band gap and tunable optoelectronic properties. However, changing these properties by bending of the DBP structure has yet to be investigated. Herein, we report the synthesis, optoelectronic, and structural properties of (2, 7)dibenzo[ a, e ]pentalenophanes with four different bridge sizes and bending angles of the DBP unit, accompanied by (TD)DFT calculations. The last, strain‐inducing dehydration reaction was accomplished by using Burgess' reagent. The HOMO and LUMO levels and the magnetic shielding of protons pointing inside the cyclophane cavity grew stepwise with increasing ring strain. Single‐crystal X‐ray structures of the smallest three derivatives revealed a near semi‐circle and a bend angle of the DBP unit of almost 88° for the smallest derivative. We demonstrated the synthetic versatility of our approach by varying the substituents at the DBP unit, allowing for further tuning of optoelectronic properties. The synthetic strategy presented herein may pave the way for the synthesis of conjugated DBP nanorings. Abstract : Bend me if you can : Bent dibenzo[ a, e ]pentalenes (DBPs) were synthesized through incorporation into a cyclic structure. The last, strain‐inducing dehydration reaction was accomplished by using Burgess' reagent. Single‐crystal X‐ray structures revealed a near semi‐circle and bend angle of the DBP unit of up to 88°. The synthetic strategy presented herein may pave the way for the synthesis of conjugated DBP nanorings.